Importance of ground refuges for the biodiversity in agricultural hedgerows. (January 2017) - Lecq, S.; Loisel, A.; Brischoux, F.; Mullin, S.J.; Bonnet, X.
Highlights: In agroecosystems ground refuges at the base of hedgerows represent key habitats for many animals. We used non-lethal rapid biodiversity assessments to sample various morphospecies in hedgerows. We used co-inertia analyses, a functional index, and predator abundance to compare hedgerows. Ground refuge availability markedly influenced biodiversity and predator abundance. Surveys and replanting programs should integrate ground refuges as key elements. Abstract: In most agro-ecosystems, hedgerows provide important habitat for many species. Unfortunately, large scale destruction of hedges has stripped this structure from many landscapes. Replanting programs have attempted to restore hedgerow habitats, but the methods employed often fail to replace the unique microhabitats (complex matrix of stones, logs and roots found along the base of the hedge) that provided key refuges to an array of animal species. We examined the influence of ground refuges on animal diversity in an agricultural landscape. We used non-lethal rapid biodiversity assessments to sample invertebrate and vertebrate taxa in 69 hedges having different levels of herbaceous cover, tree cover, and refuge availability. Co-inertia analyses compared hedge characteristics with the animal biodiversity sampled. We also used a functional index (accounting for body mass, trophic level, and metabolic mode of the species sampled) to compare hedges. In addition, large sedentary predators (e.g. snakes) were used as indicators of shelter presence/quality and as bio-indicators of food web structures. Finally we used unbiased Chao-estimates to evaluate species richness. All results were convergent and show that complexity of the base of the hedge (e.g., bank size and stone abundance) positively influenced biodiversity and predator abundance. Guidelines to restore hedgerows should integrate refuges that can be constructed by retaining the materials that are extracted during the planting of the hedges.